STRUCTURAL ANALYSIS OF CULMIFEROUS MATERIAL SURFACE UNDER MICROWAVE RADIATION TREATMENT - Maxim N. Moskovskiy; Rudolf A. Fridrikh; Anatoly A. Gulyayev (Advanced Engineering Research)
Application of culmiferous waste as fractionated strawy litter in the poultry plant under floor housing is considered. Optimal parameters of the initial culmiferous material processing by microwave radiation treatment are specified. Qualitative changes of structural straw surface are investigated.